Hormone replacement therapy. The cardiologist’s point of view - Peruga, Jan Z.; Kopff, Anna; Krzemińska-Pakuła, Maria (Menopause Review/Przegląd Menopauzalny, 2007)
Current knowledge on hormone replacement therapy, its usage and influence on the cardiovascular system in postmenopausal woman is discussed in the article.